2023
DOI: 10.3390/biom13010118
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Rescues TNF-α-Inhibited Proliferation, Migration, and Osteogenic/Odontogenic Differentiation of Dental Pulp Stem Cells

Abstract: Strategies to promote dental pulp stem cells (DPSCs) functions including proliferation, migration, pro-angiogenic effects, and odontogenic/osteogenic differentiation are in urgent need to restore pulpitis-damaged dentin/pulp regeneration and DPSCs-based bone tissue engineering applications. Cannabidiol (CBD), an active component of Cannabis sativa has shown anti-inflammation, chemotactic, anti-microbial, and tissue regenerative potentials. Based on these facts, this study aimed to analyze the effect of CBD on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The time course of ribosome assembly in cells overexpressing DbpA(R331A) showed a slower rate of the overall 50S subunit assembly than that expressing wild-type DbpA (Gentry et al, 2016). Although they could be measured in the 30S peak of the sucrose gradient at 1 mM Mg 2+ , 27S and 35S were not identi ed from either the front or the latter part of the 30S peak through cryoEM analysis in our previous studies, probably due to their low abundance and small size as early pre50S intermediates (Gentry et al, 2016;Yu et al, 2023). Unlike 27S and 35S, both the 45S peak at 1 mM Mg 2+ and pre50S peak at 10 mM Mg 2+ showed clear pre50S particles with varies conformation in this study (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The time course of ribosome assembly in cells overexpressing DbpA(R331A) showed a slower rate of the overall 50S subunit assembly than that expressing wild-type DbpA (Gentry et al, 2016). Although they could be measured in the 30S peak of the sucrose gradient at 1 mM Mg 2+ , 27S and 35S were not identi ed from either the front or the latter part of the 30S peak through cryoEM analysis in our previous studies, probably due to their low abundance and small size as early pre50S intermediates (Gentry et al, 2016;Yu et al, 2023). Unlike 27S and 35S, both the 45S peak at 1 mM Mg 2+ and pre50S peak at 10 mM Mg 2+ showed clear pre50S particles with varies conformation in this study (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Our recent studies on the structural distortion of the 30S subunit at different Mg 2+ concentrations also revealed that mature ribosomes exhibit structural instability at low Mg 2+ concentrations, mainly manifested in increased exibility of h17, h44, and rRNA helices and ribosomal proteins in decoding center (Yu et al, 2023). These ndings suggested that special attention must be paid to maintaining Mg 2+ concentration when studying ribosomes, especially ribosome precursors.…”
Section: Discussionmentioning
confidence: 91%
“…In 2023, research was carried out to evaluate the influence of CBD on the migration and differentiation of pulp stem cells and it was observed that CBD attenuated the production of proinflammatory cytokines stimulated by TNF-alpha in pulp stem cells; This information corroborates the hypothesis that CBD is a possible therapeutic agent to treat pulpitis and promote dentin/pulp regeneration in regenerative cell therapy techniques within the field of endodontics, although additional investigations are still needed (Yu et al, 2023). There is even a cannabinoid-Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.17, n.5, p. 01-13, 2024 based medicine in the patent process that aims to treat and prevent dental pulp diseases (Stahl, 2023).…”
Section: Introductionmentioning
confidence: 71%
“…DPSCs can also migrate to the lesion site to differentiate into target cells to repair the injured tissue. However, studies have shown that MSCs may be transformed in response to cytokines in the inflammatory environment, and thus lose their immunomodulatory ability [187]. The effect of an inflammatory microenvironment on MSCs in autoimmune diseases needs further study.…”
Section: Discussionmentioning
confidence: 99%